Reise zum Ararat - Parrot, Christoph Friedrich, 1791-1841 (My University, 1834)
In 1829, Estonian explorer Friedrich Parrot led the first successful modern expedition to climb Mount Ararat (5,137m), fulfilling a lifelong goal. Accompanied by Armenian writer Khachatur Abovian, the team reached the summit on September 27, 1829, overcoming skepticism that the mountain was unconquerable. The expedition established scientific mountaineering in the region
Von Christoph Friedrich Parrot. - Berlin : Haude und Spenerschen Buchhandlung, 1834. - Vol. ; 24 cm. - 2 v. in 1
Vol. 1. Reise-beschreibung, 1834 ; 262 s. : 1 Karte ; Vol. 2. Wissenschaftliche abhandlungen, 1834 ; 198 s. : 2 Taf.
Keywords: Ararat, Mount-Description and travel